BRAND AUTHENTICITY: A STUDY ON ITS IMPACT ON BRAND LOYALTY THROUGH BRAND RELATIONSHIP QUALITY IN THE LOCAL FOOTWEAR INDUSTRY - Marshella Tristandinata; Nurrani Kusumawati (Ikatan Dosen Menulis, 2024)
This study investigates the impact of brand authenticity (BA) on brand loyalty in the local footwear industry, using brand relationship quality as a mediating factor. Building on Lee and Chung's (2020) framework, the research identifies key attributes of brand authenticity (BA)—product authenticity, communication authenticity, brand originality, and price authenticity—and examines their impact on brand loyalty through brand relationship quality, specifically brand satisfaction, trust, and commitment. A mixed-methods approach was employed. The study first conducted a quantitative analysis using an online survey and PLS-SEM to examine the relationships between the brand authenticity attributes, brand relationship quality, and subsequently, brand loyalty. This was followed by qualitative semi-structured interviews, analyzed through thematic coding, to validate and elaborate on the quantitative findings and confirm the key BA attributes in the local footwear context. The study confirmed that product authenticity, encompassing design newness and product originality, enhances brand satisfaction, trust, and commitment. Communication authenticity, encompassing advertising authenticity and company authenticity, positively affects satisfaction and trust, while brand originality impacts satisfaction and commitment. Price authenticity enhances satisfaction and trust but does not significantly influence long-term commitment. The results indicate that brand satisfaction and commitment mediate the relationship between BA and brand loyalty, while brand trust does not. The research offers practical insights for local footwear brands to enhance authenticity and build stronger consumer relationships by focusing on original product designs, transparent communication, a distinctive brand story and image, and fair pricing practices. Theoretical implications include validating and adapting Lee and Chung's (2020) framework for the footwear industry, contributing industry-specific insights into the role of brand authenticity in shaping consumer loyalty within the local Indonesian footwear sector, guiding future research and brand management strategies.